Association of HbA1c with functional outcome by ischemic stroke subtypes and age - Jeong, Jihyun; Park, Jae Kyung; Koh, Young Ho; Park, Jong-Moo; Bae, Hee-Joon; Yun, Sang-Moon (Frontiers in Neurology, 2023)
Objectives: To determine whether high HbA1c levels are related to short-and long-term functional outcomes in patients with ischemic stroke (IS) and whether this association differs according to the IS subtype and the patient's age.The data of 7,380 IS patients admitted to 16 hospitals or regional stroke centers in South-Korea, between May 2017 and December 2019, were obtained from the Clinical Research Collaboration for Stroke-Korea-National Institute of Health database and retrospectively analyzed. Among these patients, 4,598 were followed-up for one-year. The HbA1c levels were classified into three groups (<5.7%, 5.7% to <6.5%, ≥6.5%). Short-and long-term poor functional outcomes were defined using the modified Rankin Scale score of 2 to 6 at three-months and one-year, respectively. IS subtypes were categorized according to the Trial of ORG 10172 in Acute Stroke Treatment (TOAST) classification.Results: There was an association between higher HbA1c (≥6.5%) and poor functional outcomes at three-months in all patients (three-months; OR, 1.299, 95% CI 1.098, 1.535, one-year; OR, 1.181, 95% CI 0.952, 1.465). When grouped by age, the associations after both 3 months and 1 year observed in younger adult group (<65 years), but not in group aged 65 years and older (three-months; <65 years